Conception of Social Justice in Eastern Indonesia within the Framework of the Republic of Indonesia - Anak Agung Gede Oka Wisnumurti; I Putu Eka Mahardhika; I Gusti Agung Ayu Yuliartika Dewi (Iapa Proceedings Conference, 2019)
The country of Indonesia, which has abundant natural resources, with diverse tribes, races, religions, cultures, customs and thousands of islands that we often hear, the term jambrud equator is one of the many words that praise the richness of the archipelago. If you look at the data from the Central Statistics Agency (BPS) in 2018 about the human development index in Indonesia, the trend has experienced a good increase in 2018 at 71.39%, with a trend in a period of almost a decade. from 2010-2018 experienced an average national growth of 0.88%, the highest position was occupied by DKI Jakarta Province with the human development index figure at 80.47% with 0.51% growth from 2017-2018 and the lowest was occupied by the Papua Province with 60, 64% position with 1.64% growth from 2017-2018. This research uses a conceptual approach. The conclusion in this study is that social justice in Indonesia which has a Pancasila ideology foundation provides a comprehensive concept of justice space, covering all sectors of national and state life that must be carried out by all citizens of the nation. In order to create comprehensive justice, the State must attend and have a scale of development priorities so that eastern Indonesia can have a quality of life that is equivalent to the population of Indonesia in the west.social justice